The Effect of E-Learning on Self-Care Behaviors of People with Type 2 Diabetes Mellitus in Babol - Seyed Jalil Seyedi-Andi; Hasan Heidari; Somayyeh Sefidhaji; Mohammad Ghanbari (Iranian Association of Health Education and Health Promotion, 2018)
Background and Objective: Diabetes is a common chronic diseases that different factors play an important role in controlling it as well as in its patients' self-care behaviors. The Survey shows the traditional cares performed so far have not been enough. The purpose of the present study is to investigate the effect of electronic education on self-care behaviors among the patients with type II diabetes who were a member of Babol Diabetes Association. Methods: The present research was a controlled intervention study conducted on 180 people with diabetes. These patients were assigned to two groups of 90 through simple random sampling: the case group and the control group. Only the case group were trained through electronic method for 3 months. The information about the patients' self-care behaviors were collected in both pre-intervention and post-intervention phases using the standard diabetes self-care questionnaire and the data were analyzed using SPSS as well as descriptive tests (Frequency, Percentage, Mean, Standard Deviation) and analytic statistical tests (Chi-Square and Paired T-test). Results: The results showed that there was a significant difference between the mean self-care scores acquired before and 3 months after the educational intervention (0/001< P). The mean self-care score acquired 3 months after the educational intervention increased in the case group, in as much as it had statistically significant difference (0/001< P). The mean self-care score acquired 3 months after the educational intervention decreased in the control group, so that it had statistically significant difference in a reverse order (0/001> P). Conclusion: The electronic education has a positive effect on self-care behaviors of patients with diabetes, and the patients' mean self-care score improves.